PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII5 SMP NEGERI 8 PEKANBARU - Nelvita Febrina Hasan; Zulkarnain Zulkarnain; Putri Yuanita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is a class action research that aims to improve the learning process and to increase mathematics achievement from the student’s with applied Discovery Learning model. The research was conducted in class VIII5 SMP Negeri 8 Pekanbaru in the even semester of the 2018/2019 academic year. The subject of this research consist of 39 students, there are 19 male students and 20 female students. This research has two cycles with each cycle has three meetings and one test. The instruments used in this research were learning instruments and the instruments of collecting data. The learning instruments used include syllabus, lesson plan, and student work sheets. The instruments of collecting data were observation sheets and learning outcome test. The data analysis of students and teacher activity showed that the learning process has improved after the discovery learning model being implemented. The data of the student’s evaluation test showed that the persentage of students reached the Minimum Mastery Criteria (MMC) increase from the basic score to first test, from first test to second test. The results of this research showed an increasing of students achievement where the basic score 10,3% to the first test 38,5%, the second test 761,5%. For the skills achievement score of the first test 33,3%, the second test 59,0%. This research concludes that the implementation of Discovery Learning improved the learning process and the student’s mathematical achievement at class VIII5 SMP Negeri 8 Pekanbaru.Key Words: Mathematics Achievement, Discovery Learning Model, Class Action Research